Hungary : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2005 Article IV Consultation highlights that Hungary's economy achieved valuable gains in 2004 with GDP growth recovering to 4 percent. The growth was supported by strong investment and robust export growth. Consumption slowed in response to rising unemployment, a moderation in wage growth and a tightening of the housing subsidy scheme. Despite these favorable developments, risks associated with the twin deficits remained. Although some fiscal consolidation has taken place, the twice upward-revised fiscal deficit target was not met.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet